1999
DOI: 10.1046/j.1365-2958.1999.01304.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid domains of mycobacteria studied with fluorescent molecular probes

Abstract: SummaryThe complex mycobacterial cell envelope is recognized as a critical factor in our failure to control tuberculosis, leprosy and other non-tuberculous pathogens. Although its composition has been extensively determined, many details regarding the organization of the envelope remain uncertain. This is particularly so for the non-covalently bound lipids, whose natural

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(81 citation statements)
references
References 23 publications
(29 reference statements)
3
78
0
Order By: Relevance
“…24,25) The two dyes showed slightly different staining patterns: Similar annular images were obtained, but different staining patterns were seen in the septa. About 40% of the cells' septa stained with Nile Red (Table 1), whereas fDHPE staining was observed in only about one half of these septa (Table 1, Fig.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…24,25) The two dyes showed slightly different staining patterns: Similar annular images were obtained, but different staining patterns were seen in the septa. About 40% of the cells' septa stained with Nile Red (Table 1), whereas fDHPE staining was observed in only about one half of these septa (Table 1, Fig.…”
Section: Resultsmentioning
confidence: 55%
“…The hydrophobic fluorescent dye Nile Red also stains hydrophobic structures, including intracellular cytoplasmic membranes and lipid droplets. 24,25) Differences between the hydrophobicity and molecular size of DHPEs and Nile Red are expected to result in different membrane staining properties. To determine the staining specificity of fluorescent DHPEs, we performed double-staining of rDHPE and Van-FL.…”
Section: Discussionmentioning
confidence: 99%
“…Organized lipid microdomains in live mycobacteria were reported in 1999 (38), using fluorescent lipid probes. More recently, cardiolipin enrichment was observed at the septa and poles of actively growing cells with the fluorescent dye 10-N-nonyl acridine orange (39).…”
Section: Discussionmentioning
confidence: 99%
“…Differential scanning calorimetry demonstrated that a major portion of these lipids occurred in a structure of extremely low fluidity in the growing cells, which may account for the low permeability (Liu et al, 1995). Electron spin resonance techniques (Liu et al, 1995(Liu et al, , 1996 and fluorescent molecular probes (Christensen et al, 1999) provided further evidence for a lipidic bilayer located externally to the conventional plasma membrane and organized into lipid domains of different hydrophobicity and permeability features. The asymmetric lipid bilayer, extremely impermeable to hydrophilic and hydrophobic compounds, corresponds to a mycobacterial external membrane, in a way analogous to the outer membrane (OM) in Gramnegative bacteria (Christensen et al, 1999).…”
Section: Abbreviationsmentioning
confidence: 99%